Sentinel surveillance of influenza-like-illness in two cities of the tropical country of Ecuador: 2006-2010. - Richard W Douce; Washington Aleman; Wilson Chicaiza-Ayala; Cesar Madrid; Merly Sovero; Franklin Delgado; Mireya Rodas; Julia Ampuero; Gloria Chauca; Juan Perez; Josefina Garcia; Tadeusz Kochel; et al. (PLoS ONE)
Background Tropical countries are thought to play an important role in the global behavior of respiratory infections such as influenza. The tropical country of Ecuador has almost no documentation of the causes of acute respiratory infections. The objectives of this study were to identify the viral agents associated with influenza like illness (ILI) in Ecuador, describe what strains of influenza were circulating in the region along with their epidemiologic characteristics, and perform molecular characterization of those strains. Methodology/findings This is a prospective surveillance study of the causes of ILI based on viral culture of oropharyngeal specimens and case report forms obtained in hospitals from two cities of Ecuador over 4 years. Out of 1,702 cases of ILI, nine viral agents were detected in 597 patients. During the time of the study, seven genetic variants of influenza circulated in Ecuador, causing six periods of increased activity. There appeared to be more heterogeneity in the cause of ILI in the tropical city of Guayaquil when compared with the Andean city of Quito. Conclusions/significance This was the most extensive documentation of the viral causes of ILI in Ecuador to date. Influenza was a common cause of ILI in Ecuador, causing more than one outbreak per year. There was no well defined influenza season although there were periods of time when no influenza was detected alternating with epidemics of different variant strains.